Emergency liver transplantation after Kasai portoenterostomy. Issue 2 (February 1994) - Corbally, M T; Heaton, N; Rela, M; Mieli-Vergani, G; Portmann, B; Mowat, A; Williams, R; Tan, K C
Abstract : Three patients with stable liver function after Kasai portoenterostomy developed acute liver failure secondary to liver necrosis. Doppler ultrasound at presentation revealed reversed diastolic hepatic arterial blood flow. Two patients survived after urgent liver transplantation. Liver necrosis should be suspected in children with chronic liver disease presenting with fever and rapidly deteriorating liver function.